THE EFFECT OF FRAUD TRIANGLE ON FINANCIAL STATEMENT FRAUD IN BANKING COMPANIES - Stevansyah, Nikita; Suhendah, Rousilita (International Journal of Application on Economics and Business, 2023)
The purpose of this study is to find empirical evidence on the effects of financial stability, external pressure, financial objective, ineffective supervision, and rationality on financial statement fraud. The population of this study are banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. This study uses data from 75 banking companies selected using the purposive sampling method. The data in this study were analyzed using EViews 12 Student Version software and the data analysis method used was multiple linear regression. The results of this study show that financial stability and rationality have a negative and significant impact on financial reporting fraud. On the other hand, the external pressures, the financial objective, and ineffective supervision do not have a significant impact on the fraud of the financial statements.